Efficacy and immune activation of ipilimumab in early-stage lung cancer patients - Noguchi, Shingo; Yatera, Kazuhiro (Journal of Thoracic Disease, 2018)
Immune checkpoint inhibitors, such as cytotoxic T-lymphocyte antigen 4 (CTLA-4) antibody and programmed death-1 (PD-1) antibody, improve the prognosis in several types of cancer patients, and they modulate the effector T-cell activation, proliferation and function (1).